The Study On The Applicability Of AHO-CORASICK Algorithm In Identifying Tests’ Validity - Ed O. Omictin III; Rodrigo Gante Jr; Robby Rosa P. Villaflores; Ma. Bryne Catherine M. Marchan; Rodolfo T. Noblefranca Jr (Universitas Kristen Duta Wacana, 2012)
Aho-Corasick Algorithm (ACA) is a kind of dictionary-matching algorithm that locates elements of finite set of strings within an input text. It matches all patterns “at once”, so the complexity of the algorithm is linear in the length of the patterns plus the length of the searched text plus the number of output matches. This paper discusses the applicability of Aho-Corasick algorithm in identifying test validity using the standard Guidelines in Evaluating Tests. A proposed Quiz-Zone system was developed in order to evaluate and test the applicability of the algorithm used. Quiz-Zone allows the user to create exam that will check the test’s validity. It also allows the user to choose five types of exam namely: Matching Type, Multiple Choice, Essay, True or False and Short-Answer. The researchers revealed that there are some rules in identifying test validity that ACA can’t be applied. Keywords : Aho Corasick Algorithm, string-matching algorithm, test validity